Harnessing the Power of Data to Improve Family Justice: A New Nuffield Family Justice Observatory For England and Wales. (18th July 2019) - Broadhurst, Karen; Williams, Teresa
Abstract : A pilot Family Justice Observatory for England and Wales is being launched in Spring 2019. Its overarching aim is to address concerns about the limited and uncertain place of empirical evidence in the family justice system. The Observatory will focus on providing intelligence about how the system is working, especially through the accelerated use of electronic population level data on family justice cases. Drawing on collaborative relationships between data providers and users, as well as policy and practice colleagues, the Observatory will improve collective understanding of the needs of children and families and how they are met by the family justice system. Key Points for the Family Court Community: Decisions made in the family courts have lifelong effects on the lives of children and families. However, there is insufficient research evidence about the immediate and longer‐term outcomes of family court decisions as an international trend. Greater use of large‐scale datasets produced routinely by the family courts and related agencies can shed light on the impact of family court decisions, addressing questions of both transparency in family court practice and effectiveness. Administrative data refers to information about persons or organizational activity that is collected routinely by government, statutory, or other agencies. The advantages of using administrative data for socio‐legal research lie in sample size, electronic format, and that records often date back a number of years. Use of this data is an efficient means of generating intelligence about how family justice systems are working, and where researchers can be provided with safe access to anonymised records. Looking ahead, the further digitization of not only records but also services will create even richer data resources for socio‐legal research.